2018
DOI: 10.1123/jmld.2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Spontaneous Leg Movement Patterns Between Infants With Typical Development and Infants at Risk for Developmental Delay: Cross-sectional Observation Prior to Sitting Onset

Abstract: Purpose: To investigate differences in the patterns of supine spontaneous leg movements produced before sitting onset between infants with typical development (TD) and infants at risk for developmental delay (AR). Method: Cross-sectional, observational study. Thirty-five infants were included, 18 infants with TD (130.4 ±38.0 days) and 17 infants AR (124.1± 65.7 days). Infants were placed in the supine position and video taped for 4 to 5 minutes while in an alert, content state. After the recording, videos we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…We chose these four dimensions as these are among the most commonly used parameters to measure infant movement. Previous literature demonstrated these parameters showed differences between infants with TD and infants at risk of AR, and between infants with various developmental outcomes (Abrishami et al, 2019;Deng et al, 2018;Shida-tokeshi et al, 2018;Zuzarte et al, 2020). Since this was the first time that a barcoding method was applied to capture multi-dimensionality of leg movements in infants, we separated each variable into a dichotomous system for a relatively easy interpretation.…”
Section: Barcoding Analysismentioning
confidence: 99%
“…We chose these four dimensions as these are among the most commonly used parameters to measure infant movement. Previous literature demonstrated these parameters showed differences between infants with TD and infants at risk of AR, and between infants with various developmental outcomes (Abrishami et al, 2019;Deng et al, 2018;Shida-tokeshi et al, 2018;Zuzarte et al, 2020). Since this was the first time that a barcoding method was applied to capture multi-dimensionality of leg movements in infants, we separated each variable into a dichotomous system for a relatively easy interpretation.…”
Section: Barcoding Analysismentioning
confidence: 99%
“…22 Although the current body of work is yet to establish the individual significance of these movement parameters, subsequent publications used these markers to distinguish between infants with TD and those at risk for developmental disability (AR). 17,23 Here, we report the quantity and kinematic characteristics of leg movements in a single symptomatic child with SMA type I (2 copies of SMN2) treated with disease-modifying therapy at 6 months and 15 days of age. Sensors captured data for a full day (8-13 hours) at 8 different time points across 12.5 months.…”
Section: What This Evidence Addsmentioning
confidence: 99%
“…For each movement, peak acceleration, average acceleration, and duration are computed and averaged across all movements to summarize daily movement characteristics 22. Although the current body of work is yet to establish the individual significance of these movement parameters, subsequent publications used these markers to distinguish between infants with TD and those at risk for developmental disability (AR) 17,23…”
Section: Introductionmentioning
confidence: 99%
“…After which at 6 months they are capable of banging and shaking toys ( Gerber et al, 2010 ). It has been shown that in comparison to their typically developing counterparts, infants born at risk exhibit less refined control of their upper and lower body functions when it comes to actions such as kicking ( Heathcock et al, 2005 ; Deng et al, 2018 ), reaching ( van der Heide et al, 2005 ; Guimarães et al, 2013 ), and grasping ( de Almeida Soares et al, 2014 ). With an understanding of infant milestones and how their performance differs between typically developing and at-risk infants, it can be concluded that a smart toy that can distinguish these groups should be capable of identifying the various interactions seen at these milestones.…”
Section: Introductionmentioning
confidence: 99%